Quadruple Helix Innovation Model for Rural Development: The Case of Sukaraja Tourist Village in Indonesia - Widjajani Widjajani; Arnia Fajarwati; Asep Hidayat; Dudi Haryadi (Lembaga Penelitian Universitas Langlangbuana, 2018)
Tourist villages in Indonesia have a very important role in rural development. The village is the smallest unit of rural development in Indonesia that has its own autonomy in management. Even though there are many innovation models have been well developed in some parts of the world, but it has yet to be implemented in Indonesia. Quadruple helix innovation model has been introduced in developed countries to develop their countries. Thus, this model is seen suitable to be adapted in some villages in Indonesia to achieve prosperity and to improve the welfare of Indonesian society. In general, this research is aimed to adapt the quadruple helix innovation model for the tourist village in Tasikmalaya, West Java, Indonesia. Specifically, this research is aimed to (1) identify the driver for the village development, (2) examine the process of village development, and (3) adapt a model of the village process development. The design for this research is a case study. This case study is conducted in a Sukaraja tourist village in Tasikmalaya, West Java that is chosen purposely. Sukaraja Village is chosen as a study location because it has economic potential in terms of tourism and handicrafts. From the existing condition of socioeconomic and cultural in Sukaraja Village this study adapts a quadruple helix innovation model using soft system methodology to achieve prosperity and to improve the welfare of the village community. The results of this study show that (1) the driver for the village development is a tourism industry that have to manage professionally, therefore have to run by village-owned enterprise (2) the process of village development is a holistic process and cannot be done just by single institution, and (3) the model of process development called a quadruple helix innovation model, which is using synergies from four institutions in the village, there are the village government, the village industries, the village education system and the village industrial community. As a whole, the quadruple helix innovation model can be used to improve village welfare communities and in turn will enhance the prosperity of Indonesian society as a whole.